Best principal management of school mission and instructional programs of secondary schools in Banda Aceh, Indonesia - Salleh, Mohamad Johdi; Hatta, Muhammad (IJSRP.ORG, 2013)

(untitled)
The main focus of the study is to analyze the principals’ management of school mission and instructional programs of secondary schools in Banda Aceh, Indonesia. The framework of the study is based on the models by Dwyer (1984), Hallinger and Murphy (1985), and, Latip (2006). Data was collected using survey methods and the questionnaires are the main tool of the study. Questionnaires used were the Principal Instructional Management Rating Scale (PIMRS) that had been adopted from Hallinger and Murphy (1985). One hundred and sixty three teachers and twelve principals of twelve public secondary schools in Banda Aceh were chosen as the respondents of the study. The data gathered from the survey was analyzed using descriptive and inference statistics of the SPSS-Versions 16.0 programme. The findings show that the principals of secondary schools in Banda Acheh had practiced the highest on ‘Monitoring Student Progress’ as perceived both by teachers and the principals themselves. It is hoped that this research will provide useful findings which will effectively assist the innovation of instructional leadership quality among principals and teachers of secondary schools in Banda Aceh in order to enhance students' academic performance.